The battle of the Labyrinth - Riordan, Rick. (New York : Hyperion Books for Children, 2008)
When demonic cheerleaders invade his high school, Percy Jackson hurries to Camp Half Blood, from whence he and his demigod friends set out on a quest through the Labyrinth, while the war between the Olympians and the evil Titan lord Kronos draws near.
Keywords: Mythology, Greek -- Juvenile fiction; Labyrinths -- Juvenile fiction; Camps -- Juvenile fiction; Monsters -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Mythology, Greek -- Fiction; Labyrinths -- Fiction; Camps -- Fiction; Monsters -- Fiction; Animals, Mythical -- Fiction; Titans (Mythology) -- Fiction; Fantasy fiction